Effectiveness of psidium guajava leaves volatile oil extracts in providing relief from dental pain in exposed dental pulp of rats - Caga, Joanna Marie R.; De Jesus, Jessamine DC.; Serraon, Antolin P. (Co-author).; De Castro, Elizabeth (Adviser).
Guava (Psidium guajava), an indigenous plant in the Philippines, has many ethno medicinal uses. One of its known medical use, was chewing the fresh leaves to provide relief for toothache. It was yet established whether its pure extract (e.g., volatile or aqueous extract) was effective as analgesic for pulpitis. The study tested the volatile oil extract's effectiveness as an analgesic. Furthermore, it served as a supportive study to the potential of Guava leaves oil extracts as an alternative medicine to toothache. METHODS: The volatile oil extraction method was used. A total of 15 male Sprague-Dawley rats were put under general anesthesia, the pulps were exposed and the following treatments were administered: 800 mg/kg Guava leaves volatile oil extracts and Eugenol. The amount of food consumed by the rats before pulp exposure, after pulp exposure, and after treatment were collected and measured in grams. Data were analyzed by Minitab software. The statistical tests used were ANOVA, Paired T-test and Two Sample t-test. RESULTS: After pulp exposure, a decrease in food consumption was observed among the 40 mg/kg no treatment groups. Following the application of treatment (40 mg/kg and Eugenol), there was an increase in the amount of food consumption of the rats but the applications of the 800 mg/kg caused no increase in food consumption of the rats. CONCLUSION: The Guava leaf volatile oil extract 800 mg/kg concentration was not effective as an analgesic but the results of the pilot study suggest that the 40 mg/kg concentration of extract was effective.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.